ANALISIS PERKEMBANGAN INDUSTRI HALAL INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - Muhamad Wardany Anwar; Budi Suharto (ITB AAS Indonesia Surakarta, 2026)
This study analyzes the development of Indonesia's halal industry from an Islamic economic perspective, focusing on the integration of digital innovation and sustainability principles in the post-mandatory halal certification era. Grounded in the philosophical foundations of Islamic economics, which views the halal industry as a pivotal instrument for achieving falah (comprehensive well-being) and adhering to halalan-tayyiban principles, the research explores the industry's significant growth and regulatory transformation in Indonesia. A qualitative approach with an exploratory case study design is employed, utilizing in-depth interviews with key stakeholders and secondary data from official reports, research institutions, and academic journals. The data analysis is conducted thematically to identify key patterns and policy implications. The findings reveal that Indonesia has maintained a strong position in the global Islamic economy (ranking 2-4 in the SGIE Report 2021-2023), with a domestic halal market value reaching USD 318.91 billion in 2024 and projected Muslim consumer spending of USD 281.6 billion by 2025. However, a significant challenge lies in the low rate of halal certification among Micro, Small, and Medium Enterprises (MSMEs), with only 28.8% of food and beverage MSMEs certified as of February 2025. The discussion highlights how Islamic economic principles, particularly Maqasid Shariah and Halal Supply Chain Management (HSCM), drive the industry's ethical and operational frameworks. It also emphasizes the crucial role of digital innovations like Blockchain and Artificial Intelligence in enhancing transparency and trust. This study addresses existing research gaps by offering a comprehensive analysis of the synergy between regulation, technology, and Islamic economic values, providing a holistic understanding of how Indonesia can optimize its halal industry potential for adaptive, competitive, inclusive, and sustainable growth in the global market.